2000
DOI: 10.1007/s007010050453
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for Interbody Fusion With Threaded Titanium Cages at Cervical and Lumbar Levels. Results on 357 Cases

Abstract: Cervical and lumbar interbody fusions with threaded titanium cages appear to be efficacious with few complications. Long term follow-up (4 years cervical, 7 years lumbar) confirms that impression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 25 publications
3
42
0
10
Order By: Relevance
“…These results verify previous findings showing that the measurement method influences determinations of surgery outcome [17]. Despite a more functional evaluation in the present study, the differences with respect to other long-term evaluations [4,9,13,14,23] might be explained by the use of a prospective rather than retrospective design. Retrospective studies have limited potential for firm conclusions regarding the effectiveness of a specific treatment.…”
Section: -Year 2-yearsupporting
confidence: 88%
“…These results verify previous findings showing that the measurement method influences determinations of surgery outcome [17]. Despite a more functional evaluation in the present study, the differences with respect to other long-term evaluations [4,9,13,14,23] might be explained by the use of a prospective rather than retrospective design. Retrospective studies have limited potential for firm conclusions regarding the effectiveness of a specific treatment.…”
Section: -Year 2-yearsupporting
confidence: 88%
“…With the introduction of different interbody fusion devices, such as cages, surgical strategies have been evolved to achieve anterior cervical fusion. The studies on such promising techniques have been published thereafter 7,12,15,17) . However, Wigfield 18) , in a thorough literature review, concluded that there was limited evidence supporting the use of a cervical interbody fusion device in place of autologous bone.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of interbody fusion include direct removal of the dysfunctional disc and preservation or restoration of the disc height [39]. Thus, these devices allow the restore and maintenance of disk space height and normal sagittal contours by stimulating the vertebrae to grow together into one solid bone.…”
Section: Chitosan-based Intervertebral Fusion Cagesmentioning
confidence: 99%